Hubungan Pengetahuan dan Sikap dengan Perilaku Masyarakat tentang Pemberantasan Sarang Nyamuk Demam Berdarah Dengue (DBD) - Ika Espiana; Rizky Muji Lestari; Fitriani Ningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Dengue Hemorrhagic Fever (DHF) is one disease that contributes to the death rate to date. This could be due to a lack of knowledge and attitudes so that people's behavior has not been maximized in carrying out Mosquito Nest Eradication (PSN). Currently, PSN activities are still not maximally carried out by the community, so the Aedes aegypti mosquito breeding is increasingly widespread. To determine the correlation between knowledge and attitudes with community behavior regarding eradicating mosquito nests with dengue hemorrhagic fever (DHF) and using the literature review research method. Search journals using an academic database, namely Google Scholar, published in 2017-2020 using Indonesian and obtained six research results according to the inclusion criteria. The research design used in the article is Cross-Sectional. The results obtained from 6 related articles that five pieces stated that there was a correlation between knowledge and attitudes toward community behavior regarding the eradication of mosquito nests with dengue hemorrhagic fever (DHF) with an average p-value <0.05 and 1 article did not correlate. There is a relationship between knowledge and attitudes toward community behavior regarding eradicating mosquito nests with dengue hemorrhagic fever (DHF). This is because respondents who have good knowledge and positive attitudes tend to behave well.